A angústia de Prometeu: a Crítica Literária e os conflitos de Harold Bloom - Lima, Luiz Fernando Martins de [UNESP] (2014)
The present Doctoral Dissertation was written guided by three main aims, which are: to investigate the nature, statutes, limitations of and claims made by Literary Criticism and Theory; that being done, to carry out a survey of all the critical and theoretical publications by professor Harold Bloom (1930), from Yale University – eminent and controversial figure of Literary Studies nowadays – by means of expounding, collecting the wealth of critical acclaim of, and commenting on every work. The analysis of the twenty one books presented points out three predominant phases in the critic´s career: a phase in which studies of English Romanticism prevail, the phase of the development of the anxiety of influence theory, and the phase of the literary canon defense outside the Universities; at last, the third aim is to analyze one work of Criticism by each one of the phases pointed out – namely The Visionary Company (1961), Poetry and Repression (1976) and How to Read and Why (2000), respectively – in order to identify the foundations of Harold Bloom´s agonistic criticism and its rivals. By the end, it will be possible to verify that Harold Bloom´s critical performances always offered themselves as alternatives to major Literary Criticism trends that prevail or had prevailed in American Literary Studies: New Criticism, Deconstruction and Cultural Studies